Reading Tabriz Municipality Building Based on Foucault’s Theory of Power - Noushin Ghorbani; Sahar Toufan; Habib Shah Hosseini; Nima Vali Zadeh; Hassan Sattari Sarbangholi (صفه)
The first Pahlavi Era coincided with many changes and developments that led to the advent of modern Iran. Reza Shah tried to institutionalise power in society based on a new political rationality. To do so, he needed obedient and disciplined citizens to achieve sovereignty. According to Foucault, the famous French philosopher, the modern form of power differs from its traditional. He believes that modern power has tacitly influenced all society layers, and controlled the behaviour of large populations by bringing discipline. In this case, Foucault points to some techniques that create discipline in the space. The question here is how architectural space played a vital role in implementing power in the first Pahlavi era from the Foucauldian perspective of power theory. The extant study aimed at matching the spatial configuration of Tabriz Municipality Building with Foucault's spatial discipline techniques. The research was conducted based on the descriptive-analytical method, and data analysis was done through Depthmap software. According to results obtained from VGA indices (including visual integration, visual control, entropy, coherence, and depth), the location of the main entrance of the building, spatial articulation, settings of walls, the arrangement of rooms along narrow corridors, and transparent room doors were consistent with disciplinary techniques introduced by Foucault. The features mentioned above could play a significant role in visual and physical control of the interiors of a building, as well as creating a spatial discipline. The results pointed to a pattern that can be used in the design of public buildings by city managers.